PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, KARAKTERISTIK INFORMASI SISTEM AKUNTANSI MANAJEMEN, DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA MANAJERIAL - Ammar Naufal Nugraha; Banu Witono (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to examine the influence of information technology utilization, management accounting information system characteristics, and environmental uncertainty on managerial performance in the banking sector in Solo City. The research applied a quantitative approach with a causal explanatory design. Data were collected through questionnaires distributed to 92 respondents from 11 banks, determined using the Slovin formula with a 10% margin of error and convenience sampling. Variables were measured using a five-point Likert scale. Validity was tested through correlation analysis, and reliability was measured using statistical methods. Data analysis included classical assumption tests and multiple linear regression to assess both partial and simultaneous effects. The results show that all three independent variables information technology utilization, management accounting information characteristics, and environmental uncertainty have a positive effect on managerial performance. These findings indicate that enhancing IT usage, improving the quality of management accounting information, and adapting to environmental uncertainty can contribute to better managerial performance in the banking industry.